Pendampingan Usaha Ekonomi bagi Ibu PKK dalam Pembuatan Sabun Cuci Piring di Desa Sonorejo, Kecamatan Padangan, Kabupaten Bojonegoro - Mohammad Tsaqibul Fikri; Sahri; Ifa Khoiria Ningrum; Agus Sholahudin Shidiq (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Sonorejo village is one of the villages located in the Padangan sub-district, whose people are mostly farmers. Given the needs and social welfare need to be improved. One of the factors that Human Resources cannot develop is due to lack of knowledge and understanding. Therefore, there needs to be empowerment for their own resources, one of which is empowerment for PKK mothers in terms of making dish soap. The aim and target of this service is to hope that PKK mothers will have the motivation to be entrepreneurship, thus forming independent group members to produce dish soap, as well as being more productive, creative and responsive fans.